Canine Albumin Polymorphisms and Their Impact on Drug Plasma Protein Binding - Costa, Ana P.; Court, Michael H.; Burke, Neal S.; Zhu, Zhaohui; Mealey, Katrina L.; Villarino, Nicolas F. (Drug metabolism and disposition, 2019)
Drug binding to plasma proteins is routinely determined during drug development. Albumin polymorphisms c.1075G>T (p.Ala359Ser) and c.1422A>T (p.Glu474Asp) were previously shown to alter plasma protein binding of a drug candidate (D01-4582, 4-[1-[3-chloro-4-[N′-(2-methylphenyl)ureido]phenylacetyl]-(4S)-fluoro-(2S)-pyrrolidine-2-yl]methoxybenzoic acid) in a colony of Beagles. Our study investigated the hypothesis that drug-protein binding in plasma from dogs with the albumin H1 (reference) allele would be greater than in plasma from dogs with the albumin H2 allele (c.1075G>T and c.1422A>T) (n = 6 per group). The plasma protein binding extent of four drugs (D01-4582, celecoxib, mycophenolic acid, and meloxicam) was evaluated using ultracentrifugation or equilibrium dialysis. Free and total drug concentrations were analyzed by liquid chromatography–mass spectrometry. The albumin gene coding region was sequenced in 100 dogs to detect novel gene variants, and H1/H2 allele frequency was determined in a large and varied population (n = 1446 from 61 breeds and mixed-breed dogs). For meloxicam, H1 allele plasma had statistically significant higher free drug fractions (P = 0.041) than H2 allele plasma. No significant difference was identified for plasma protein binding of D01-4582, celecoxib, or mycophenolic acid. c.1075G>T and c.1422A>T were the most common single nucleotide polymorphisms in canine albumin, present concurrently in most study dogs and occasionally identified independently. Our findings suggest a potential influence of c.1075G>T and c.1422A>T on plasma protein binding. This influence should be confirmed in vivo and for additional drugs. Based on our results, albumin genotyping should be considered for canine research subjects to improve interpretation of pharmacokinetic data generated during the drug development process for humans and dogs.